Conceptual process-oriented model of reengineering in the construction sector - STELMAKH, Oleksandr; HULIAIEV, Dmytro; PEDKO, Yurii; YELIN, Volodymyr (Ways to Improve Construction Efficiency, 2025)
The conceptual process-oriented model of reengineering in the construction sector is a fundamental approach to transforming business processes in the construction industry to enhance their efficiency, productivity, and competitiveness. It is based on the use of modern process management methodologies, including the identification, analysis, optimization, and implementation of innovative changes in the production and management mechanisms of construction companies. The primary objective of this model is not only to improve individual aspects of activity but also to ensure a holistic approach to managing all components of business processes, including interactions between structural divisions, suppliers, contractors, and clients. The process-oriented approach to reengineering in the construction sector is founded on principles of radical restructuring of operational and management procedures to achieve significant improvements in cost, quality, execution speed, and adaptability to market changes. The use of Business Process Management (BPM) methodology enables the systematization and automation of processes, reduction of inefficiencies, cost minimization, and an increased level of control over project execution. A key tool for implementing this conceptual model is the use of digital technologies, including Building Information Modeling (BIM), which enhances design accuracy, optimizes costs, and reduces risks. Another important element is the integration of quality management systems, ensuring compliance with regulatory requirements and increasing the reliability of construction output. The effective implementation of the conceptual process-oriented model of reengineering requires a thorough analysis of the current state of business processes, identification of bottlenecks, and the formation of a strategic vision for change. A crucial component is the adoption of agile management principles, which allow for rapid adaptation to changing market conditions and regulatory requirements. Moreover, implementing such a model necessitates a high level of personnel competence and an organizational culture focused on continuous improvement. The application of reengineering in the construction sector enables increased project execution efficiency, cost reduction, optimization of resource allocation, and improved interaction among all process participants. Thus, the conceptual process-oriented model of reengineering in the construction sector is a necessary prerequisite for improving project management efficiency, modernizing business processes, and achieving sustainable industry development. It provides construction companies with strategic advantages through the integration of modern technologies, process automation, and adaptation to the dynamic changes of the market environment.